Combination Of Avocado Seed Powder And Commercial Feed On The Growth And Survival Of Bileh Fish Seed (Rasbora sp.) - Muliyana, Agusriati; S, Irhami; Rahmayanti, Fitria; Muktaridha, Muktaridha (Universitas Teuku Umar, 2024)
The combination of Avocado Seed Powder and Commercial Feed on the Growth Rate of Bileh Fish as an Alternative to Support Bileh Fish Farming. This study aims to determine the growth rate of bileh fish (Rasbora sp.) fed with a combination of avocado seed powder and commercial feed and to identify the optimal dose of the combination for bileh fish cultivation. The research was experimental, using a Completely Randomized Design (CRD) with three treatments and three repetitions. The treatments included different doses of the combination of avocado seed powder and commercial feed: P0 = 100% commercial feed (control), P1 = 90% commercial feed/10% avocado seed powder, P2 = 80% commercial feed/20% avocado seed powder, and P3 = 70% commercial feed / 30% avocado seed powder. The research stages consisted of preparing containers, collecting bileh fish, preparing experimental feed, conducting maintenance and observation, and collecting data. The data collected included absolute weight gain, absolute length gain, specific growth rate (SGR), and survival rate (SR) of Rasbora fish. The data were processed and analyzed using the F-test (ANOVA). The results show that the best dosage of the feed combination for Rasbora fish is treatment P3, with an absolute weight gain of 0,35%/day, a daily length growth rate of 0,4%/day, a specific growth rate (SGR) of 1,89%/day, and a survival rate (SR) of 99%.